2001
DOI: 10.1016/s0014-5793(01)02741-7
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐state NMR investigations of interaction contributions that determine the alignment of helical polypeptides in biological membranes

Abstract: Helical peptides reconstituted into oriented phospholipid bilayers were studied by proton-decoupled 15 N solid-state NMR spectroscopy. Whereas hydrophobic channel peptides, such as the N-terminal region of Vpu of HIV-1, adopt transmembrane orientations, amphipathic peptide antibiotics are oriented parallel to the bilayer surface. The interaction contributions that determine the alignment of helical peptides in lipid membranes were analysed using model sequences, and peptides that change their topology in a pH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Experiments with this latter technique also indicated that the in-plane-transmembrane transition is reversible (19). Interestingly, in this study all peptides exhibiting high transfection efficiencies also show pH-dependent membrane alignments with transition midpoints around pH 6 (16,17). This suggests that pH-dependent membrane insertion of the peptides constitutes an important part of the DNA import mechanism.…”
Section: Discussionsupporting
confidence: 55%
“…Experiments with this latter technique also indicated that the in-plane-transmembrane transition is reversible (19). Interestingly, in this study all peptides exhibiting high transfection efficiencies also show pH-dependent membrane alignments with transition midpoints around pH 6 (16,17). This suggests that pH-dependent membrane insertion of the peptides constitutes an important part of the DNA import mechanism.…”
Section: Discussionsupporting
confidence: 55%
“…6C) that could attach or even insert into the membrane (70,71). This region is conserved in YidC homologs that do not have a P1D, suggesting an important and conserved role of this region for the function of YidC (see above).…”
Section: Resultsmentioning
confidence: 99%
“…Thermodynamic analysis of the binding of pentaeptides to model lipid bilayers and the partition of tripeptides between water and octanol also indicates that Ala has a slight preference for the lipid-water interface region over the acyl chain region (17). Solid-state NMR studies of peptide-bilayer interactions point in the same direction (33). It thus appears that the interactions between a nascent polypeptide chain and the ER translocon that determine membrane protein topology in vivo are remarkably similar to peptide-lipid interactions in highly simplified in vitro systems.…”
Section: Ala Residues Extend Outside the Membrane In L 13mentioning
confidence: 88%